2010
DOI: 10.5194/acp-10-2975-2010
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-mediated coastal particle formation: an overview of the Reactive Halogens in the Marine Boundary Layer (RHaMBLe) Roscoff coastal study

Abstract: Abstract. This paper presents a summary of the measurements made during the heavily-instrumented Reactive Halogens in the Marine Boundary Layer (RHaMBLe) coastal study in Roscoff on the North West coast of France throughout September 2006. It was clearly demonstrated that iodinemediated coastal particle formation occurs, driven by daytime low tide emission of molecular iodine, I 2 , by macroalgal species fully or partially exposed by the receding waterline. Ultrafine particle concentrations strongly correlate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 86 publications
10
105
0
1
Order By: Relevance
“…Observed concentrations are significantly lower than at coastal locations and with little annual variation (Mahajan et al, 2010). Observations performed during dedicated campaigns at Tenerife and Cape Verde (Read et al, 2008) reported concentrations between 0.2 and 4 pptv.…”
Section: Introductionmentioning
confidence: 99%
“…Observed concentrations are significantly lower than at coastal locations and with little annual variation (Mahajan et al, 2010). Observations performed during dedicated campaigns at Tenerife and Cape Verde (Read et al, 2008) reported concentrations between 0.2 and 4 pptv.…”
Section: Introductionmentioning
confidence: 99%
“…coastal regions with strong emissions of iodine from macroalgae; McFiggans, 2005), although this process, and its impact on local O 3 concentrations, is not yet completely understood. Recent work has shown increased O 3 deposition velocities during low tides, owing to direct deposition to macroalgae and/or to O 3 involvement in iodine-mediated particle formation (McFiggans et al, 2010).…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…Nevertheless, there is some observational evidence of considerable particle nucleation within the MBL in regions with enhanced DMS flux (Davison et al, 1996;O'Dowd et al, 1997;Clarke et al, 1998). In this context, the Southern Ocean surrounding the Antarctic continent shows striking biological activity during polar spring and summer (Gabric et al, 2005;Korhonen et al, 2008;Lana et al, 2011), provoking pronounced formation of biogenic sulfur aerosol (Minikin et al, 1998;Preunkert et al, 2007). Accordingly, nucleation events have also been reported from coastal Syowa (Ito, 1993) and the rather coastal Finnish Antarctic station Aboa (73 • 03 S, 13 • 25 W, 130 km away from coastline; Koponen et al, 2003), while at continental South Pole comparable events had to be typically associated with the impact local pollution during calm weather conditions (Park et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, as pointed out in a noted review about Antarctic aerosol by Shaw (1988), it is remarkable that submicrometer particles are present throughout the Antarctic air, in spite of distant source regions and efficient wet depositional removal within the persistent circumpolar low pressure system. In fact, the Southern Ocean remains as being by far the dominant source to the Antarctic aerosol body, making atmospheric sea salt and biogenic sulfur to the major aerosol components (Wagenbach, 1996;Minikin et al, 1998;Preunkert et al, 2007). Nowadays, minor anthropogenic R. Weller et al: Characterization of the variations of condensation particle concentrations emissions arising from fossil fuel combustion during research and tourism activities might be considered as well (Shirsat and Graf, 2009).…”
Section: Introductionmentioning
confidence: 99%